A detailed kinetic investigation on the effects of hydrogen enrichment on the performance of gas-fueled SI engine. Issue 10 (8th August 2016) - Salavati-Zadeh, Ali; Javaheri, Ahmad; Ghavami, Seyed Vahid; Esfahanian, Vahid; Tehrani, Masoud Masih; Akbari, Hossein
ABSTRACT: This study investigates the effects of hydrogen enrichment on formation of pollutants and greenhouse gases in gas-fueled spark ignition engines. To this end, a previously validated detailed mechanism is embedded with a comprehensive one-dimensional engine model and the results are verified with experimental observations at different compression ratios and engine loads. The simulations are then performed for different mixtures of hydrogen and natural gas. The results indicate that adding hydrogen increases the cylinder peak pressure at different loads and compression ratios, despite the fact that reduces the amount of carbon monoxide, carbon dioxide, and methane in all the conditions.